(3eNGdaGJ bhGYO GdSdhc hYbhHGJgG ddYScQjjf HhRGQI GdOGNdjI (B=s Violations of the rules of conduct, and punishments thereto, applicable on the military personnel at the Ministry of Interior : ((3GdeNGdaGJ(B-(3GdYbhHGJ(B-(3GdELQGAGJ(B) /s - (3YHO GdeWdH, eeOhM YHO GdMejO,s 1955-; (3UjGe, hdGA gGOjs ((3GdTGQbI, GdEeGQGJ GdYQHjI GdeJMOI (B:s (3TQWI GdTGQbI, eQcR HMhK GdTQWI,s, 2009)
(3jJfGhd GdcJGH ehVhY eNGdaGJ bhGYO GdSdhc hYbhHGJgG ddYScQjjf HhRGQI GdOGNdjI ef NdGd YOI eMGhQ, cGdELQGAGJ GdJCOjHjI, CfhGY GdLRGAGJ GdJCOjHjI CaQGO hELQGAGJ GdJMbjb hGdeMGceI, ELQGAGJ GdeNGdaGJ GdedcjI GdHSjWI hGdeTOOI, GNJUGUGJ JhbjY GdLRGAGJ, Gdhba Yf GdYed hbO Je YQV GdeGOI GdYdejI HCSdhH GbJUQ Ydi YQV GdbhGYO GdbGfhfjI ddJCOjH ef fUhU hELQGAGJ heMGceGJ hcPdc Je EOQGL cGaI GdbQGQGJ GdhRGQjI GdNGUI HgPg GdbhGYO(B. (3hHPdc jYO GdcJGH EVGaI Edi GdecJHI GdCefjI hGdTQWjI, hRGOG eYQajG Edi cGaI GdYScQjjf GdYGedjf HhRGQI GdOGNdjI GdPjf fCed GSJaGOJge ef gPG GdLgO GdeJhGVY(B.s
Keywords: (3GdEeGQGJ GdYQHjI GdeJMOI(B.s -- 9; (3ShA Sdhc QLGd GdTQWIs -- (3bhGfjf hJTQjYGJs -- (3GdEeGQGJ GdYQHjI GdeJMOIs; (3QLGd GdTQWIs -- (3GdEeGQGJ GdYQHjI GdeJMOIs -- (3JCOjHs